The Acts of The Apostles: Fact or Fiction? - Chandra Han (Diligentia: Journal of Theology and Christian Education, 2020)
Acts of the Apostles is unique in the Bible. It serves as the transition between the Gospel and the Epistles. For Christians, Acts of the Apostles is a historical book that presents the fact of how Christianity is then widespread. Within the historical issues in the studies of Acts, one creative approach is to classify Acts as a Greco-Roman novel that is highly fictional, a popular treatise for entertainment purposes. The aim of this paper is to examine the historicity of the Acts. The issues of the historicity of the text, the reliability of sources used by Luke, chronology, and data accuracy will be examined. Here, I will argue that Luke’s theological-historical perspective to explain the passage is still better than the novel perspective. I will also demonstrate that the theological principles derived from the novel perspective are strongly disputed compared to those of the theological-historical perspective. Only several theological principles of the text from both historical novel and theological-historical perspective will be presented.